Nutritional Assessment of Children and Adolescents with Atypical Anorexia Nervosa: A Preliminary Longitudinal Investigation Using the 24-h Dietary Recall - Beatrice Valeriani; Jacopo Pruccoli; Francesca Chiavarino; Maria Letizia Petio; Antonia Parmeggiani (MDPI AG, 2024)
Background: Atypical Anorexia Nervosa (AAN) is a Feeding and Eating Disorder characterized by fear of gaining weight and body image disturbance, in the absence of significantly low body weight. AAN may present specific clinical and psychopathological features. Nonetheless, the literature lacks data concerning the nutritional characteristics and body composition of children and adolescents with AAN and their variation over time. Methods: Case series, including 17 children and adolescents with AAN. All the patients were assessed at the first evaluation (T0) with a standardized dietary assessment (24 h Dietary Recall, 24 hDR). Nutritional data were compared with European dietary reference values (DRVs). Body composition parameters (weight, fat mass, fat-free mass) and their changes over time at two (T1) and six (T2) months were collected as well, using a Bioelectrical impedance analysis (Wunder WBA300 with four poles and foot contact; impedance frequency 50 kHz 500 μA; impedance measurement range 200~1000 Ω/0.1 Ω). Results: The included individuals presented eating behaviors oriented towards significantly low daily energy intake (p < 0.001) compared with DRVs set by the European Food Safety Authority (EFSA) (with low carbohydrates and fats), and increased proteins (p < 0.001). A longer latency before observation (illness duration before observation) correlated with a negative change in weight. Body composition parameters were described, with no significant changes across the six-month outpatient assessment. Discussion: This is the first research to systematically assess the body composition and nutritional features of a group of individuals with AAN in the developmental age. Further research should assess the effect of targeted treatment interventions on body composition and nutritional features.